Water and Wastewater Treatment in Africa – Current Practices and Challenges. Issue 8 (26th November 2013) - Wang, Hongtao; Wang, Tao; Zhang, Bingru; Li, Fengting; Toure, Brahima; Omosa, Isaiah Bosire; Chiramba, Thomas; Abdel‐Monem, Mohamed; Pradhan, Mahesh
<x xml:space="preserve">Abstract</x> Sustainable access to safe drinking water and basic sanitation is an important part of the millennium development goals (MDGs). For most African countries, an extensive effort is needed for the last three remaining years for the achievement of the MDGs, especially in Sub‐Saharan Africa. Current practices for water and wastewater treatment in Africa are insufficient to ensure safe water and basic sanitation. To address this challenge, joint efforts are needed, including transforming to green economy, innovating technologies, improving operation and maintenance, harvesting energy, improving governance and management, promoting public participation, and establishing water quality standards.